Move Analysis in Students’ Writing - Ika Lusi Kristanti; Afi Ni’amah (Tell : Teaching of English Language and Literature Journal, 2020)
Discourse analysis is one of linguistics branches that concerns in language use. Discourse can be written and spoken. Written discourse can be found in students’ writing, especially in writing report text. In term, moves analysis is applied to recognize the rhetorical composition of text. The researchers want to describe the phenomenon deals with the students’ moves in writing, especially in report text. Research design used in this research is descriptive qualitative research. The result shows that there were fourteen data that used the two moves patterns. Most students used this pattern to present information about something to the readers. Their texts dealt with social phenomena in people environment, mainly: animal. Actually, students used the first move pattern that was in line with the generic structure of report text, such as: general classification and description. In this term, general classification dealt with the phenomenon. Whereas, description related with two terms, such as: parts and habits or behavior. In sum, there are two students’ moves in writing, mainly: general classification and description.